MORPHOLOGICAL CHARACTERISTICS AND WATER STATUS OF SOME TUNISIAN BARLEY GENOTYPES SUBMITTED TO WATER STRESS - Mansouri; Radhouane (International Journal of Research -GRANTHAALAYAH, 2015)
Tunisia has been qualified as a country vulnerable to climate change that will be unregistered a great drop of annual rainfall and an increase of evaporation. Response strategies of agriculture to drought will be critical because drought is one of the major abiotic stresses which adversely affect crop growth and yield. Among strategies to be developed to cope with the effect of climate change, recourse of genetic diversity and new varietal creation can be a solution among other methods. In this study, four barley genotypes were cultivated in semi-controlled conditions and submitted to three levels of water stress. Data were recorded on number of grain per plant (NGP), one thousand grains weight (PMG), total leaf surface (TLS), plant height (HAT), stomata density (DS), leaf water content (RWC) and leaf water potential (LWP). Results showed that morphological characteristics (HAT, TLS, DS), yield components (NGP, PMG) and water status (LWP, RWC) of barley genotypes were decreased significantly. However, moderate water deficit didn’t affect significantly the most of parameters studied. Study had demonstrated also that barley genotypes developed different strategies and mechanisms to cope with water deficit, based essentially on their osmotic adjustment capacity.